2011
DOI: 10.1002/chem.201100072
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Organocatalysis at Work: Functionalization of Hollow Periodic Mesoporous Organosilica Spheres with MacMillan Catalyst

Abstract: Halogenbrücken sind nichtkovalente Wechselwirkungen, in denen Halogenatome als elektrophile Spezies auftreten. Die Energien und geometrischen Charakteristika derartiger Bindungen werden im vorliegenden Kurzaufsatz beschrieben, und es wird diskutiert, welche Voraussetzungen Moleküle erfüllen müssen, um diese Wechselwirkungen eingehen zu können. Die Bildung von Halogenbrücken wirkt sich auf alle Forschungsgebiete aus, die durch molekulare Erkennung und Selbstorganisation bestimmt sind. Es werden einige Prinzipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 68 publications
(24 reference statements)
0
70
0
Order By: Relevance
“…The PMHSsupported MacMillan catalyst 5 favorably compares to other immobilized imidazolinones, for which the recycle was realized only on two or three reruns [10][11][12][13] or the observed enantioselectivities were lower than those obtained with the nonsupported MacMillan catalyst (Table 3). 14,15 In conclusion, it was shown that catalysts derived from PMHSsupported imidazolidinone 5 and different acids can be conveniently employed to promote Diels-Alder cycloadditions of a,b-unsaturated aldehydes with cyclopentadiene. The supported catalysts behaved very similarly to their non-supported counterparts in terms of enantioselectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PMHSsupported MacMillan catalyst 5 favorably compares to other immobilized imidazolinones, for which the recycle was realized only on two or three reruns [10][11][12][13] or the observed enantioselectivities were lower than those obtained with the nonsupported MacMillan catalyst (Table 3). 14,15 In conclusion, it was shown that catalysts derived from PMHSsupported imidazolidinone 5 and different acids can be conveniently employed to promote Diels-Alder cycloadditions of a,b-unsaturated aldehydes with cyclopentadiene. The supported catalysts behaved very similarly to their non-supported counterparts in terms of enantioselectivity.…”
mentioning
confidence: 99%
“…Given its popularity, it is not surprising that it has been covalently immobilized on different supports. [10][11][12][13][14][15] Despite this variety of proposed solutions, however, the development of an easily available, inexpensive, recyclable and truly chemical and stereochemical efficient MacMillan catalyst still has to be realized. Among the major drawbacks still to be properly addressed and solved we can mention the lower enantioselectivities with respect to that of the non-supported system and the issue of the recyclability.…”
mentioning
confidence: 99%
“…Furthermore, the supported catalyst should be catalytically comparable or superior to its homogeneous counterpart and easily recovered and reused many times with unchanged activity and selectivity. [2] Magnetic nanoparticles (MNPs) have recently emerged as sustainable catalyst supports [3][4][5] owing to their easy functionalization and synthesis, low toxicity, large surface area, facile separation via magnetic force with high dispersion property in organic solvents. Therefore, the development of an easy and straightforward strategy for immobilization of organocatalysts on magnetic nanosupports may facilitate the use of organocatalytic processes for industrial applications.…”
mentioning
confidence: 99%
“…Reproduced with permission. [ 308 ] Ever-more enriched chemical versatilities of MONs will endow the materials with more functionalities to satisfy various applications. [ 321,[338][339][340] Gehring et al incorporated sulfonic acid ( R -SO 3 H) into the framework of organosilica to fabricate solid acids with superacid properties, which showed promising applications in heterogeneous catalysis and the antibacterial fi eld.…”
Section: Mons For Other Specifi C Applications In Nanotechnologymentioning
confidence: 99%
“…[ 299 ] HPMOs were synthesized by a hard-templating method using spherical hematite NPs as the templates ( Figure 33 a). [ 308 ] The MacMillan catalyst was further immobilized into the mesopores of HPMOs via a co-condensation process and "click chemistry". For comparison, the MacMillan catalyst was immobilized by a post-grafting process (Figure 33 b).…”
Section: Mons For Catalytic Applicationsmentioning
confidence: 99%